Embryo adoption: Some further considerations. (February 2015) - Patterson, Colin
<x content-type="archive" xml:space="preserve">Abstract</x> Recent discussions of embryo adoption have sought to make sense of the teaching of the Congregation for the Doctrine of the Faith (CDF) document Dignitas personae which appeared to provide a negative judgment on such a practice. This article aims to provide a personalist account of the process of fertilization and implantation that might serve as the basis for the negative judgment of the CDF document. In doing so, it relies upon the idea that a person, including an embryo, is not to be considered in isolation, but always in relation to God and to others. This approach extends the substantialist conceptualizations commonly employed in discussions of this issue. More generally, the article seeks to highlight the value of a personalist re-framing for an understanding of the moral questions surrounding the beginning of life. Lay summary: This article seeks to make sense of what appears to be a clear-cut rejection, set out in the Congregation for the Doctrine of the Faith (CDF) document Dignitas personae, of the proposal for women to "adopt" surplus frozen embryos. It draws upon more recently developed modes of philosophical/theological reasoning to argue that, in human procreation, both fertilization and implantation represent constitutive dimensions of divine creative activity and so must be protected from manipulative technological intervention. Since embryo adoption requires this kind of technology, it makes sense for the Church document not to approve it.